Effect of defect density and energy level mismatch on the performance of perovskite solar cells by numerical simulation - Jamal M.S.; Shahahmadi S.A.; Chelvanathan P.; Asim N.; Misran H.; Hossain M.I.; Amin N.; Sopian K.; Akhtaruzzaman M. (Elsevier GmbH, 2023)
Computer simulation; Defect density; Lead compounds; Nickel oxide; Numerical models; Perovskite; Solar cells; Defect energy level; Defect levels; Hole transport materials; Interfacial defect; Organic-inorganic; Perovskite layers; Power conversion efficiencies; SCAPS-1D; Perovskite solar cells